Risk Analysis Of Jakarta Pramuka Market Area Management To Improve Customer Satisfaction - Sunandar, Ali; Alfian, Muhammad Agfi (Journal of World Conference (JWC), 2020)
This research dilator behind how big the influence of risk factors that exist in the Jakarta scout market area to increase customer satisfaction. This study aims to determine the dominant factors causing management risks that exist in the Jakarta scout market area related to increased customer satisfaction. This study aims to determine the dominant factors causing the management risks that exist in the Scouting Market Area to obtain some of the most influential risks and develop strategies to be able to increase customer satisfaction in the Scouting Market Area. The study used a survey method in the form of asking questions to several respondents. This survey was conducted by distributing questionnaires and interviews with relevant parties that were used as a source of information. From the results of data processing with a statistical data processing application, several high risks have an impact on customer satisfaction and get a strategy to reduce these impacts.